2019
DOI: 10.4174/astr.2019.97.2.74
|View full text |Cite
|
Sign up to set email alerts
|

Colonic hypoperfusion following ligation of the inferior mesenteric artery in rectosigmoid colon cancer patients

Abstract: Purpose Colon perfusion status is one of the most important factors for the determination of postoperative anastomotic complications. Colonic hypoperfusion can be induced by inferior mesenteric artery (IMA) ligation in some patients. This study aimed to evaluate atherosclerotic risk assessment and vascular parameters of CT angiography as predictors of colonic hypoperfusion. Methods This prospective study was conducted at a tertiary referral hospital and included 46 rect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…The HT is credited for ease of lymph node dissection (LND) around IMA for staging and oncological outcome plus tension-free anastomosis of the remaining colon. 3 , 4 The compromise of blood supply leading to colon ischemia, 5 hypoperfusion and anastomotic leakage (AL), 6 , 7 damage to superior hypogastric plexus, 8 and genitourinary defecatory functions 9 are some concerns for the HT. The LT has shown a decrease in leakage with the comparable oncological outcome and 5-year long-term survival.…”
Section: Introductionmentioning
confidence: 99%
“…The HT is credited for ease of lymph node dissection (LND) around IMA for staging and oncological outcome plus tension-free anastomosis of the remaining colon. 3 , 4 The compromise of blood supply leading to colon ischemia, 5 hypoperfusion and anastomotic leakage (AL), 6 , 7 damage to superior hypogastric plexus, 8 and genitourinary defecatory functions 9 are some concerns for the HT. The LT has shown a decrease in leakage with the comparable oncological outcome and 5-year long-term survival.…”
Section: Introductionmentioning
confidence: 99%
“…One of reasons for anastomotic complications is able to explain with poor perfusion in the anastomosis site[ 1 - 5 ]. It is known that about 10% of the population has poorly developed collateral circulation branches around the splenic flexure of the colon[ 6 - 9 ]. Due to the differences in vascular structure, the resection and anastomosis in the poorly perfused colonic area may lead to postoperative colonic hypoperfusion[ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The preservation of LCA during anterior resection for rectal cancer requires exposing IMA and LCA, which if of technical difficulties. Thus, preoperative evaluation of the IMA type based on three-dimensional CT reconstruction results is beneficial [15,37]. In this study, the IMA of 108 patients was divided into four types according to the three-dimensional CT reconstruction image.…”
Section: Discussionmentioning
confidence: 99%
“…Sorelius et al reported that high ligation of IMA disrupted LCA blood supply, resulting in decreased mesenteric blood supply and increased risk of colonic necrosis after rectal cancer surgery [14]. It has been suggested that atherosclerotic risk assessment and IMA length were useful predictors of the mesenteric hypoperfusion status following IMA ligation during laparoscopic rectosigmoid colon surgery [15]. In other words, mesenteric hypoperfusion is more likely to occur in patients with short IMA length or high risk of atherosclerosis after IMA ligation during laparoscopic rectosigmoid surgery.…”
Section: Introductionmentioning
confidence: 99%